Compression-based pattern recognition: an example on ECG biometrics - Carvalho, João Miguel Rafael de (2022)
The amount of data being collected by sensors and smart devices that people use on their daily lives has been increasing at higher rates than ever before. That enables the possibility of using biomedical signals in several applications, with the aid of pattern recognition algorithms in several applications. In this thesis we investigate the usage of compression based methods to perform classification using one-dimensional signals. In order to test those methods, we use as testbed example, electrocardiographic (ECG) signals and the task biometric identification. First and foremost, we introduce the notion of Kolmogorov complexity and how it relates with compression methods. Then, we explain how can these methods be useful for pattern recognition, by exploring different compression-based measures, namely, the Normalized Relative Compression, a measure based on the relative similarity between strings. For this purpose, we present finite-context models and explain the theory behind a generalized version of those models, called the extended-alphabet finite-context models, a novel contribution. Since the testbed application for the methods presented in the thesis is based on ECG signals, we explain what constitutes such a signal and the methods that should be used before data compresison can be applied to them, such as filtering and quantization. Finally, we explore the application of biometric identification using the ECG signal into more depth, making some tests regarding the acquisition of signals and benchmark different proposals based on compresison methods, namely, non-fiducial ones. We also highlight the advantages of such an alternative approach to machine learning methods, namely, low computational costs and not requiring any kind of feature extraction, making this approach easily transferable into different applications and signals.